A Study on the Line of Sight to Galaxies Detected at Gamma-Ray Energies - Amy Furniss; Josepf N. Amador; Olivier Hervet; Ollie Jackson; David A. Williams (The Astrophysical Journal Letters)
The large-scale universal structure comprises strands of dark matter and galaxies with large underdense volumes known as voids. We measure the fraction of the line of sight that intersects voids for active galactic nuclei (AGN) detected by Fermi Large Area Telescope (LAT) and quasars from the Sloan Digital Sky Survey (SDSS). This “voidiness” fraction is a rudimentary proxy for the density along the line of sight to the galaxies. The voidiness of SDSS-observed quasars (QSOs) is distinctly different from randomly distributed source populations, with a median p -value of 4.6 × 10 ^−5 and ≪1 × 10 ^−7 , when compared with 500 simulated populations with randomly simulated locations but matching redshifts in the 0.1 ≤ z < 0.4 and 0.4 ≤ z < 0.7 intervals, respectively. A similar comparison of the voidiness for LAT-detected AGN shows median p -values greater than 0.05 in each redshift interval. When comparing the SDSS QSO population to the LAT-detected AGN, we mitigate potential bias from a relationship between redshift and voidiness by comparing the LAT-detected AGN to a “redshift-matched” set of SDSS QSOs. The LAT-detected AGN between a redshift of 0.4 and 0.7 show higher voidiness compared to the redshift-matched SDSS QSO populations, with a median p -value of 2.3 × 10 ^−5 (a 4.1 σ deviation). No deviation is found when comparing the same populations between redshifts of 0.1 and 0.4 ( p > 0.05). We do not study possible causes of this voidiness difference. It might relate to propagation effects from lower magnetic or radiative background fields within voids or to an environment more favorable for gamma-ray production for AGN near voids.